Analysis of the microstructural evolution and solidification behaviour of Sn-9 wt% Zn alloy with small additions of Mg - Figueroa, Ignacio Alejandro; Novelo-Peralta, Omar; Suárez, Miguel; Lara-Rodríguez, Gabriel Angel (Journal of Mining and Metallurgy, Section B: Metallurgy, 2013)
The microstructure, solidification behaviour and hardness of Sn-9Zn-xMg (where x = 0, 0.5, 2.5 and 5 wt%) alloys were studied. The addition of 0.5 wt% did show a clear effect on the microstructure, producing three distinctive zones: a) fine eutectic structure b) coarse eutectic structure composed by large needles of Zn dispersed into a b-Sn matrix and c) small particles of the intermetallic Mg2Sn. The further additions Mg provoked that the fine eutectic structure disappeared giving place to the formation a coarse eutectic structure, large particles of Mg2Sn and Zn-rich needles. The hardness of the alloys increased with the additions of Mg. Similarly, the additions of Mg steadily drop the eutectic temperature, from 196.5ºC for the binary base alloy to 180ºC for the alloy with 5 wt% Mg. The low temperature achieved in this alloy is very close to the eutectic Sn-Pb alloy (183ºC), thus it could be a plausible substitute of the classical Pb-containing solder alloys.